Bilateral difference between lower limbs in children practicing laterally dominant vs. non-laterally dominant sports - Guan, Y.; Bredin, S.; Taunton, J.; Jiang, Q.; Wu, L.; Kaufman, K.; Wu, N.; Warburton, D. (European Journal of Sport Science, 2021)
Bilateral asymmetry in lower-limb power and dynamic balance has been associated with increased risk of sport injury, whereas there is a lack of research examining this asymmetry for child athletes. Twenty-eight fencers (19 boys and 9 girls, aged 9.71 ± 1.08 years) and 28 Taekwondo athletes (19 boys and 9 girls, aged 9.71 ± 1.08 years) were examined on the single-leg jump and Star Excursion Balance Test (SEBT) performance. A mixed model design ANOVA (2 [Sex: Boys, Girls] × 2 [Sport group: Fencing, Taekwondo] × 2 [Limb: Dominant, Non-dominant Leg]) was conducted to examine for difference for each test. There was a significant main effect of limb on hop and triple hop distance (p < 0.05). A significant limb by sex interaction (p = 0.000) was shown for the single-leg countermovement jump (CMJ) performance, wherein a bilateral difference was only shown in boys. In SEBT, a main effect (p = 0.007) of limb was identified for posterolateral (PL) reach distance. A limb by sex interaction (p = 0.009) was also shown for posteromedial (PM) reach distance, wherein a bilateral difference was only shown in girls. These findings suggest that child athletes in both laterally dominant and non-laterally dominant sports showed inter-limb asymmetry of leg power and dynamic balance. Sex should be an important consideration when evaluating bilateral difference of leg power and dynamic balance for child athletes.